ANALYSIS OF PRODUCTIVITY AND COST OF HEAVY EQUIPMENT IN GRADED PAVEMENT WORK ON THE SYAMSUDIN NOOR INTERNATIONAL AIRPORT ACCESS ROAD CONSTRUCTION PROJECT - Alfandi, Muhammad Ikhsan; Karim, Abdul (CERUCUK, 2025)
This study aims to analyze the productivity and costs of heavy equipment used in granular pavement work on the Syamsudin Noor International Airport access road construction project. The analysis focuses on evaluating the performance and cost-effectiveness of various types of equipment, including wheel loader, dump trucks,motor grade, water tanker truck and vibratory roller. Data were collected through field observations and contractor reports, which were then analyzed using productivity calculation methods and cost analysis techniques. The results show that proper equipment management and optimization significantly impact project efficiency and budget control. This research provides valuable insights for improving the planning and execution of similar infrastructure projects.Keywords: productivity, heavy equipment, cost analysis, granular pavement, airport access road